Inhibitory Effect of Sodium Citrate, Sodium Nitrite and Cinnamaldehyde on Biofilm-forming Escherichia coli O157:H7 (Journal of Environmental Bioremediation and Toxicology, 2021)
The development of biofilms by the foodborne pathogens attached to surfaces in the food processing environments results in the deterioration of products, persistence of pathogenic bacteria and transmission of food-associated diseases. In addition, biofilms are more resistant to antimicrobials than their planktonic counterparts which make their elimination from food and the food processing facilities a great challenge. This study aim was to determine the inhibitory effect of food additives on biofilm forming Escherichia coli O157:H7. The isolate obtained was subjected to Gram’s staining and various biochemical identifications and later confirmed by latex agglutination test. Biofilm formation potential was done on Congo red media and the confirmed biofilm former was subjected to biofilm formation at 10℃ and 37℃ for 168hrs. Antimicrobial susceptibility testing, MIC, MBC, and antibiofilm effect was determined following CLSI 2017 guideline. The highest zone of growth inhibition of 31 mm was exhibited by cinnamaldehyde, sodium nitrite with 26 mm and sodium citrate with 13 mm. The MIC 2.5 mg/mL was recorded for sodium citrate, 0.25 mg/mL for sodium nitrite and 0.125 μl/mL for cinnamaldehyde. Strong biofilm was formed at 37 ℃ with 7.82 x 109 CFU/mL viable cells at 168hrs while 6.79 x 109 CFU/mL were obtained at 10 ℃. All the three additives showed antibiofilm effect (at 10℃ and 37℃), cinnamaldehyde exhibited 70%-90.1%, sodium nitrite; 70%-88.2% inhibition and sodium nitrite; 75%-88% inhibition respectively. This study showed that sodium citrate, sodium nitrite and cinnamaldehyde exerted strong antimicrobial and antibiofilm properties indicating their potential as good preservatives.
Keywords: Food additives; Inhibitory effect; Antibiofilm; Cinnamaldehyde; E. coli O157:H7